Masa Peradaban Awal Harappa: Sejarah, Arsitektur, dan Tata Kota - Marlia Ujiyani, Nungki; Ipong Jazimah (Kaganga:Jurnal Pendidikan Sejarah dan Riset Sosial Humaniora, 2026)
The purpose of this research is to reconstruct historical developments, analyse architectural characteristics, and evaluate the urban planning system of Harappa as a representation of the progress of early South Asian civilisation. The method used in this research is the historical-descriptive method with heuristic stages, source criticism, interpretation, and historiography as the analytical framework. The results of the study show that the city of Harappa was founded by the Dravidian tribe and reached its peak of urbanisation in the Mature Harappa Phase (±2450–2200 BC), which was marked by architectural advances, multi-storey construction, the use of standard fired bricks, and the existence of a fort as a symbolic and administrative centre. The layout of the city of Harappa shows a consistent grid pattern, a division between the Upper City and the Lower City, and a systematically integrated drainage and clean water network. The presence of public spaces and administrative facilities further highlights the collective coordination in community life. The conclusion of this research indicates that Harappa was a unique and well-planned urban entity, reflecting technological maturity, complex urban planning systems, and established social structures in early South Asian civilisation. Keywords: Harappa, Urban Architecture, South Asian Civilization.